PJMHS 2023
DOI: 10.53350/pjmhs2023173543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on the Prevalence of Intrahepatic Cholestasis of Pregnancy

Abstract: Background: The virulent pathogen SARS-CoV-2 first appeared in the Chinese province of Hubei in December 2019. Pregnant women were a high-risk population in the pandemic because immune system alterations that occur during pregnancy make them more vulnerable to foreign infections. Late-pregnancy cholestasis is a dangerous liver condition that can cause the foetus to experience potentially fatal problems like early birth and stillbirth. In the present study we were testing the Bile acid level during pregnancy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…According to the Centers for Disease Control and Prevention (CDC), 40% of adults were avoiding medical care due to concerns related to COVID infection [24]. While there is one study showing contradictory results, comparing both conclusions is challenging due to different ethnic settings and timing [25]. In the latest study on the topic by Holden et al, the authors reported an increased incidence of COVID infection in women with ICP.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention (CDC), 40% of adults were avoiding medical care due to concerns related to COVID infection [24]. While there is one study showing contradictory results, comparing both conclusions is challenging due to different ethnic settings and timing [25]. In the latest study on the topic by Holden et al, the authors reported an increased incidence of COVID infection in women with ICP.…”
Section: Discussionmentioning
confidence: 99%